2016
DOI: 10.1007/s00299-016-2091-y
|View full text |Cite
|
Sign up to set email alerts
|

Auxin synthesis gene tms1 driven by tuber-specific promoter alters hormonal status of transgenic potato plants and their responses to exogenous phytohormones

Abstract: Ectopic auxin overproduction in transgenic potato leads to enhanced productivity accompanied with concerted and occasional changes in hormonal status, and causing altered response of transformants to exogenous auxin or cytokinin. Previously, we generated potato transformants expressing Agrobacterium-derived auxin synthesis gene tms1 driven by tuber-specific patatin gene promoter (B33-promoter). Here, we studied the endogenous hormonal status and the response to exogenous phytohormones in tms1 transformants cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 52 publications
4
30
0
Order By: Relevance
“…The most abundant CK nucleobase in the shoots in our study was iP, while in the roots it was tZ. iP was previously shown to be the most abundant CK nucleobase in potato shoots 32,33 . It has been shown that the biological activity of iP is important for physiological processes in plant shoots 43 .…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…The most abundant CK nucleobase in the shoots in our study was iP, while in the roots it was tZ. iP was previously shown to be the most abundant CK nucleobase in potato shoots 32,33 . It has been shown that the biological activity of iP is important for physiological processes in plant shoots 43 .…”
Section: Discussionsupporting
confidence: 47%
“…There is growing research interest for CK physiology in potato (Solanum tuberosum L.) due to numerous evidence for the involvement of CKs in the commercially important process of tuberisation [18][19][20][21][22][23] . A number of reports containing measurements of phytohormones in various tissues of potato plants grown in various conditions (in vitro, greenhouse) have been published so far 22,[24][25][26][27][28][29][30][31][32][33] . Data on amounts of particular molecular forms of isoprenoid CKs, as well as the auxin indole-3-acetic acid (IAA), and abscisic acid (ABA), measured in control plants in these studies, are summarised in Table 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ABA and IAA were analyzed at the Plant Physiology Laboratory, Wageningen University, the Netherlands. The extraction and analyses of ABA and IAA were done as described in Kolachevskaya et al (2017) except that the weight of the samples was 4 mg DW.…”
Section: Plant Hormone Analysismentioning
confidence: 99%
“…All StHKs demonstrated high affinity for trans -zeatin, with similar K d at the nanomolar level (Table 3). The determined K d values were close to the values of analogous constants for CK receptors of other species (Lomin et al ., 2012, 2015, Kuderová et al ., 2015) and were well correlated with concentrations of active CKs in planta (Hirose et al ., 2008) including potato (Kolachevskaya et al ., 2017, 2018).…”
Section: Resultsmentioning
confidence: 99%